Analisis Potensi Pengembangan Wisata Edukatif Berbasis Wisata Sejarah Peninggalan Kerajaan Majapahit di Trowulan Mojokerto - Afif Kurniawan Raharjo; Garsione Agni Andrea (Mataram University, 2026)
Trowulan Area, Mojokerto Regency, East Java, is the former capital of the Majapahit Kingdom and preserves numerous archaeological heritage sites, including Tikus Temple, Bajang Ratu Temple, Brahu Temple, and Gentong Temple. This study aims to analyze the potential for developing history-based educational tourism at these four archaeological sites. The research employed a descriptive qualitative approach, with data collected through participant observation, in-depth interviews, and documentation studies involving site managers, visitors, and relevant institutions. Data were analyzed using the interactive model of Miles and Huberman based on three educational tourism indicators: learning value, knowledge enrichment, and site suitability. The findings reveal that all four sites possess significant historical, architectural, and spiritual values. However, their utilization as educational tourism destinations remains suboptimal due to limited interpretive media, the absence of permanent tour guides, and inadequate supporting facilities. The study identifies seven strategic directions for development, including integrated educational tourism packages, site-based learning, cultural performances, creative economy development, digital educational tourism, tourism village development, and the establishment of an archaeological research center. The proposed recommendations include strengthening interpretive media, improving tour guide competencies, providing adequate supporting infrastructure, and fostering collaboration among government agencies, site managers, academics, and local communities to achieve sustainable history-based educational tourism centered on the legacy of the Majapahit Kingdom.